0=-14(-5x+1)

Simple and best practice solution for 0=-14(-5x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0=-14(-5x+1) equation:



0=-14(-5x+1)
We move all terms to the left:
0-(-14(-5x+1))=0
We add all the numbers together, and all the variables
-(-14(-5x+1))=0
We calculate terms in parentheses: -(-14(-5x+1)), so:
-14(-5x+1)
We multiply parentheses
70x-14
Back to the equation:
-(70x-14)
We get rid of parentheses
-70x+14=0
We move all terms containing x to the left, all other terms to the right
-70x=-14
x=-14/-70
x=1/5

See similar equations:

| -4w+5w-15w+-19=-5 | | -5(u+9)=-45 | | -6.5x+0.71=-1.89 | | -5(v+1)=-4v | | 10=f+4 | | 10n+-1=99 | | z-7−5z=2z | | 8+n/3+3=-2 | | 3(x+8)=36 | | -8+5(2x-4)=-10 | | 708+80+n=780+n | | 4x-5(3x-7)=-20 | | -6=2/3m | | 8(x+12)+9=169 | | 10x-2x=4x+2 | | 2x–6=12 | | (1/4)x+5=30 | | 4n+17=12 | | 7(x+11)+11=158 | | 2.2x–6=12 | | 10x–2x=4x+2 | | -6(x+5)=-90 | | 6(x+16)+11=149 | | 5x+-6=-146 | | 4u+3=3u | | 2m+5=5(m+7)-3m | | 8(x+12)=32 | | 2520=-360+180n | | 9=x/6-1 | | 5x2+5x−30=0 | | 8x+15=95 | | 8(x+12)=80 |

Equations solver categories